Evaluation of a community based hypertension self management education (HSME) programme in the state of Penang, Malaysia: a mixed-method study / Hanisah Mohd Yatim - Mohd Yatim, Hanisah (2017)
Hypertension poses major healthcare burdens worldwide with 1.56 billion peoples are estimated to have diagnosed with hypertension in 2025. In Malaysia, hypertension affects approximately one in three Malaysians aged 30-year-old and above; most patients have difficulties achieving good blood pressure (BP) control. Managing hypertension is challenging given the chronic nature of the disease management and the multiple daily self-care decisions that need to be made. Low self-efficacy level among the patients could have been the underlying reason for poor daily selfmanagement of hypertension, leading to suboptimal BP control. A structured, groupbased hypertension self-management education (HSME) programme could be a potential solution to improve BP control; however, the impact and effective elements of HSME programme in the Malaysian setting remain unknown. Accordingly, the main objectives of this thesis were to evaluate the impact of a structured, group-based HSME programme on the hypertensive patient's clinical and psychosocial outcomes and to explore participants' perception towards the quality and impact of HSME programme. Firstly, a HSME programme was developed, validated and pilot-tested. After that, a pre-post study design was employed to conduct the interventional study (quantitative method). Participants attended a total of 4-weekly (2-hour each session) of the HSME programme. Participant's clinical (i.e. blood pressure, lipids, weight, body mass index, waist circumference, percentage body fat and percentage skeletal muscle) and psychosocial (i.e. medication adherence, hypertension self-care behaviour, motivation, self-efficacy and quality-of-life) outcomes were assessed at baseline, post 1-week and post 2-month of HSME programme. Following the HSME programme, three focus group discussions, involving 19 participants who had attended the 4-weekly intensive HSME programme, were conducted using semi-structured moderator guide (qualitative method). Data were audio recorded, transcribed verbatim and analysed using thematic analysis approach. Forty-five participants consented to join the programme, with 36 (80.0%) attended two or more sessions. Most (68.9%) were female with a mean age of 60±7.72 years old. Post 1-week of intervention, participants were found to have significant improvement in high-density lipoprotein (HDL) cholesterol (p = 0.001), day spent on vigorous physical activity (p=0.007), motivation (p - 0.001) and self-efficacy (p = 0.005). At 2-month, participants sustained some of the aforementioned positive outcomes include HDL cholesterol, motivation and self-efficacy with other significant improvement reported in medication adherence (p = 0.005) and self-care behaviour (p = 0.002). No significant differences were found in other outcomes at all time-points. In the qualitative analysis, most participants agreed that self-management education is crucial in managing hypertension and were satisfied with the HSME programme. Participants reported to have enjoyed the group-based self-management education as support was given among peers and educators of the programme. Furthermore, information on disease management were easy to follow and more detailed compared to their normal routine follow-up with doctor at clinic or hospital. The current study findings suggested that a localised, structured educational programme should be in place to empower hypertensive patients the knowledge and skills in self-managing hypertension, providing them the confidence to sustain daily self-care activities.